Distribution and habitat of the Golden Eagle (Aquila chrysaetos) in Sonora, Mexico, 1892-2019 - Aaron D. Flesch; Ricardo Rodríguez-Estrella; Juan Pablo Gallo-Reynoso; Lucila Armenta-Méndez; Marcelino Montiel-Herrera (Revista Mexicana de Biodiversidad)
The Golden Eagle (Aquila chrysaetos) is listed as threatened in Mexico but there is little information on populations in the state of Sonora. We amalgamated 121 records of the Golden Eagle in Sonora between 1892 and 2019, including 49 observations by the authors between 1997 and 2016. Observations were from all months of the year, peaked during the breeding season and again in December with 53.7% representing likely breeding individuals. Most observations were from the Sky Islands region and Sonoran Desert of northern Sonora, with fewer from coastal west-central and especially southern Sonora. Most observations were from grasslands (34.3%), Madrean evergreen woodland (31.3%), and desert-scrub (30.3%), and very few were from subtropical forest and thorn-scrub (≤ 2.0%) suggesting preference for open vegetation communities that foster hunting. We found evidence of recent occupation of all general portions of Sonora that were occupied historically, except in central Sonora due possibly to changes in land use and land cover. Although our results suggest broad-scale distribution has been largely stable, more focused monitoring is needed to understand population trends. Large-scale urban and agricultural development, loss of grasslands and other open environments, electrocution, and poisoning pose major threats to Golden Eagles in Sonora.